Socio-Economic Impact Analysis of Rob Flooding at Kuala Dewi Indah Beach, Pantai Cermin Sub-District - Samosir, Fani Nurhadizah; Susilawati, Susilawati; Amelia, Amelia; Qur-Ani, Oktafera Halmi; Paramitha, Lydia; Andwina, Andwina (Universitas Ibn Khaldun Bogor, 2025)
Introduction: An increasingly frequent natural occurrence as a result of sea level rise and human activities near the coast is tidal flooding. One of the affected locations is Kuala Dewi Indah Beach in Pantai Cermin Sub-district, where tidal flooding has caused a number of social and economic changes in the neighborhood. Objectives: The objective of this study was to identify the social impacts and analyze the economic impacts caused by tidal flooding. Methods: Data was collected using a descriptive qualitative methodology that included a literature review, in-depth interviews and observations. Results: The research findings show that tidal flooding has impacted the economic activities of the community, resulting in considerable financial losses such as damage to boats and fishing gear. Socially, tidal flooding has caused disruption to population mobility, health and education. Conclusion: This study also highlighted the government's lack of preparedness in providing early warnings about tidal floods, with communities relying solely on word of mouth and social media. The damage caused by tidal floods is further exacerbated by the lack of community knowledge and preparedness for disasters. So it is suggested that mitigation efforts such as spatial planning, adaptable infrastructure development, and community education about disasters are necessary.